Caracterização química dos efluentes gerados pelo aterro controlado de Santa Maria e retenção de chumbo e zinco por um argissolo da depressão central do Rio Grande do Sul - Lauermann, Andressa (2007)
The environmental consequences arising from inadequate treatment of solid waste are felt directly on air, water and soil quality through contamination by the gas and leachate generated in the decomposition of the waste, in addition to heavy metals which cause serious health problems. The purpose of this study was to evaluate the impacts caused in the soil and water in an area used for the disposal of county waste, called controlled landfill of Caturrita, and the lead and zinc retention by a hapludalf located around the landfill. The evaluation of the efficiency of the process of removal of pollutants from leachate produced in the landfill, before being released in a receptor (water body), was taken by monitoring of physical, chemical and biological parameters of treatment by the system of lagoons of stabilization in the landfill (study 1). To evaluate the mobility of lead and zinc in the horizons of a Hapludalf, columns of soil from the A, E, Bt and C horizons were overlapping and submitted to surface contamination and subsequent leaching with leachate and distilled water. The concentrations of lead, zinc and other tests were determined in the outflow, collected every 5 days, and in the soil (study 2). The results showed that, except for biochemical oxygen demand (BOD), all parameters (Zn, Cu, N, P, chemical oxygen demand -COD, Na, K, C, Ca, Fe) had removed more than 50% over the treatment of the stabilization ponds, being the largest removal presented by the zinc, 91%. Despite the high removals, the values of nitrogen, phosphorus, BOD and COD found in the outflow are higher than that allowed by the legislation be released in the receptor (water body). The analysis of the outflow collected shows that concentrations of carbon, phosphorus and zinc declined over time, while copper and lead had a different behavior, where their concentrations increase by approximately the day 10, then decreasing. The soil analysis showed that the Al presented greater concentration in depth, unlike the elements Mg and K, which were concentrated in the surface soil horizons. Lead was found in greater concentration in dealing with salts, and the highest value obtained on the horizon C. Zinc has not had their behavior affected by treatments. The comparison of the concentration of the elements in the original condition of the soil with the final condition shows that, statistically, the lead was the only item that had their concentration increased in all horizons of the soil in different treatments. In dealing with salts, Al also increased in all horizons, while the Zn had only increased its concentration on the horizon A, while in treatment with leachate, the elements Zn and K also had their concentrations increased.